Serological Detection of Toxoplasmosis in Relation to marital status, Cats Contact and Abortion in Wasit province, Iraq - Zainab Abdalameer Kadhem (Academia Open, 2026)
General Background: Toxoplasma gondii represents a globally distributed protozoan parasite capable of infecting warm-blooded animals, including humans, with particular concern for pregnant women due to risks of miscarriage and congenital malformations. Specific Background: While toxoplasmosis has been extensively investigated worldwide, limited epidemiological data exist regarding its prevalence and associated risk factors among women in Wasit Province, Iraq. Knowledge Gap: The relationship between T. gondii seropositivity and socio-demographic factors such as marital status, cat contact, and abortion history remains inadequately characterized in this region. Aims: This study aimed to determine the seroprevalence of T. gondii antibodies (IgG and IgM) among women of reproductive age and examine associations with marital status, cat contact, and abortion history. Results: Among 300 women tested, 51% demonstrated seropositivity for T. gondii antibodies, with significantly higher rates observed in married women (54% vs. 30%, p=0.05) and those with abortion history (69% vs. 42%, p=0.05). Novelty: This study provides the first comprehensive assessment of toxoplasmosis seroprevalence and risk factors specifically among women in Wasit Province. Implications: These findings underscore the necessity for targeted public health interventions, including periodic screening of reproductive-age women, health education on food hygiene and cat interactions, and environmental preventive strategies to reduce T. gondii transmission.Highlight : The study found 51% seroprevalence of T. gondii antibodies among women in Wasit Province, Iraq, indicating a significant public health concern. Married women showed higher seropositivity (54%) than unmarried women (30%), linked to household exposure and contaminated food handling. Women with abortion history had elevated seroprevalence (69%), highlighting the need for routine toxoplasmosis screening in prenatal care. Keywords : Toxoplasma gondii, Seroprevalence, Reproductive Health, ELISA Diagnostic, Zoonotic Infection